FRI0441 INFECTIOUS DISEASES RISK ASSESSMENT PRIOR TO IMMUNOMODULATION THERAPY - EXPERIENCE FROM AN INFECTIOUS DISEASES UNIT. (13th June 2020) - Leal, E.; Pinheiro, H.; Betková, S.; Póvoas, D.; Estriga, A. R.; Simões, P.; Garrote, A. R.; Seixas, D.; Ramírez, F.; Manata, M. J.; Maltez, F.
Abstract : Background: The increasing use of immunomodulatory therapies has motivated the development of strategies to assess and prevent infectious diseases in these immunosuppressed patients, in whom the risk of serious infections is higher. Objectives: The aim of this study was to recognize the need to standardize prophylactic and therapeutic strategies in this population. Methods: Retrospective review of clinical files of patients evaluated in the infectious risk assessment in an outpatient clinic at the Infectious Diseases Unit at Hospital de Curry Cabral in Lisbon, between June 2016 and November 2019. We reviewed information regarding sex, age, origin, occupation, past travels as well as plans of future ones, contact with live animals, intake of unpasteurized products or unsafe drinking water, along with relevant data regarding past medical history and previous and/or ongoing treatments, including immunomodulatory ones. Results: During the established timeline, 1305 appointments were carried out, corresponding to a total of 415 patients. The majority of patients were female (263; 63.7%), the average age was 50 years and 82% were of Portuguese nationality. The most frequent groups of diseases were autoimmune/inflammatory (84.1%) and demyelinating (10.1%). At the date of the first consultation, 70% were already under immunosuppression. Screening for latent tuberculosis infection (LTBI) was done in 99% of the patients (n = 410) and treatment was proposed to 160 patients (38.5%). At the time of screening, 56, 8% of the patients were under immunossuppressive therapies, which included high doses of systemic corticosteroids (37%), anti-TNF alpha (7, 7%) and combine therapy with non-biologic agents. Active disease was diagnosed and treated in two patients. Interferon gamma release assay test (IGRA) was positive in 56.8% of patients (n = 91), negative in 32.5% (n = 52) and indeterminate in 7.5% (n=12). Of the 69 patients (43%) with indeterminate/negative or not performed IGRA, Mantoux test (TST) was positive in 48 patients. In the remainder, the treatment proposal for LTBI was based on clinical, epidemiological or radiological signs suggestive of past infection. In order to prevent hyperinfection/disseminated strongyloidiasis, 354 individuals were screened with Strongyloides stercoralis serology, of which 51 patients (14.4%) had a positive result and were treated with ivermectin. Regarding vaccination, the recommendation for annual influenza vaccination was reinforced, together with the prevention of invasive pneumococcal disease. In view of future travelling plans, vaccination against yellow fever (n = 10), meningococcal disease (n = 7), typhoid fever (n = 6), and polio (n = 2) was recommended. In cases without a previous history of measles and according to the year of birth, VASPR was prescribed to 6 patients. Vaccination to prevent herpes zoster was recommended to 20 patients. After serological evaluation, the vaccine against hepatitis A and hepatitis B was prescribed to 89 and 132 patients, respectively, the latter when serological evidence of previous vaccination or contact was absent. We identified 10 cases of positive anti-HCV antibodies, with undetectable viral load. Primary prophylaxis for Pneumocystis jirovecii pneumonia was recommended to 104 patients. Prophylaxis against reactivation of Herpes simplex infection was initiated in 4 patients. Conclusion: The decision to start immunosuppressive therapy comes with benefits and risks. Appropriate screening prior to starting therapy is an essential tool for its safe use. Referral to a specialised Infectious Risk Assessment consultation should be done promptly in order to review and address accordingly the risk of specific infections taking in to account the patients clinical and epidemiologic history. Disclosure of Interests: None declared